2021
DOI: 10.3949/ccjm.88a.20140
|View full text |Cite
|
Sign up to set email alerts
|

Coronary microvascular dysfunction: Considerations for diagnosis and treatment

Abstract: Ischemia and no obstructive coronary artery disease (INOCA) is an increasingly recognized cause of angina, and it is more commonly diagnosed in women. Coronary microvascular dysfunction (CMD), or the abnormal dilation and constriction of the small vessels of the heart, is the underlying cause of INOCA in one-half of cases. This review discusses coronary microvascular pathophysiology, considerations for invasive coronary function testing and noninvasive diagnostic modalities, implications for management, and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…Patients with INOCA report a poor quality of life and recurrent symptoms of angina, require frequent hospital admission and diagnostic interventions, and are a major burden to the health-care system 73 , 79 , 80 . Although the pathophysiology of INOCA is not fully understood, this condition is associated with endothelial dysfunction as reflected by impaired vasodilatation in response to adenosine, acetylcholine and nitroglycerin affecting mainly the microcirculation and, therefore, has a biological basis 81 . In women with MINOCA, multimodality imaging with coronary optical coherence tomography and cardiac MRI identified potential mechanisms of MINOCA in 84.5% of patients, of which 75.5% had myocardial ischaemia and 24.5% had no ischaemia, pointing equally to a biological basis for this condition 82 .…”
Section: Combined Influence Of Sex and Gender On Cvdmentioning
confidence: 99%
“…Patients with INOCA report a poor quality of life and recurrent symptoms of angina, require frequent hospital admission and diagnostic interventions, and are a major burden to the health-care system 73 , 79 , 80 . Although the pathophysiology of INOCA is not fully understood, this condition is associated with endothelial dysfunction as reflected by impaired vasodilatation in response to adenosine, acetylcholine and nitroglycerin affecting mainly the microcirculation and, therefore, has a biological basis 81 . In women with MINOCA, multimodality imaging with coronary optical coherence tomography and cardiac MRI identified potential mechanisms of MINOCA in 84.5% of patients, of which 75.5% had myocardial ischaemia and 24.5% had no ischaemia, pointing equally to a biological basis for this condition 82 .…”
Section: Combined Influence Of Sex and Gender On Cvdmentioning
confidence: 99%
“…Positron emission tomography (PET) imaging remains the standard method for estimating CFR, although single-photon emission computed tomography (SPECT), magnetic resonance imaging (MRI), intravascular Doppler ultrasound and echocardiography have been used [ 16 ]. A ratio of <2.0 at maximal hyperemia compared to baseline capacity is considered abnormal [ 17 ]. It is important to note that despite having non-obstructive CAD, patients with CMD are still at an elevated risk for major adverse cardiovascular events [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gdowski et al published a meta-analysis of 6,631 patients with suspected myocardial ischemia but without coronary artery occlusion, which showed that compared to patients with normal CFRs, CFR decreased the mortality of patients by 3.93 times, whereas the incidence of adverse cardiovascular events increased by 5.16 times ( Gdowski et al, 2020 ). Because CMVD is common in patients with cardiovascular risk factors, CFR measurements should be performed early to determine the presence of CMVD even in people without coronary artery disease to help with early diagnosis and intervention to prevent further progression of CMVD and adverse cardiac events ( Del Buono et al, 2021 ; Tjoe et al, 2021 ; Lopez et al, 2022 ). CMVD has a complex etiology, involves a wide range of people, and lacks standardized and effective means of detection, which causes the systematic prevention and management of coronary heart disease to be difficult and seriously affects the prognosis of patients.…”
Section: Clinical Significance Of Cmvdmentioning
confidence: 99%